Transitioning into Fully Blended Learning: A Model for Faculty Blended Learning Adoption - Antwi-Boampong, Ahmed (Nordic and Baltic Journal of Information & Communications Technologies, 2023)
Higher education institutions the world over is turning to Blended Learning (BL) as the preferred teaching and learning delivery approach. However, to attain campus-wide adoption requires an understanding of the influencing factors that motivate academics towards teaching in BL mode. Given this context, this paper presents findings from a qualitative study that investigates the lived experiences of academics as they adopt BL for teaching and learning in a Ghanaian university. Adopting a Grounded Theory as the methodology for this research within a sequential qualitative research design, data was collected from multiple sources. Primary data was obtained from in-depth interviews of 22 academics carried out to understand how they construct and navigate the BL teaching experiences. Secondary data was obtained from policy documents, faculty training signing sheets and Learning Management Systems (LMS) activity logs. The data was analysed using the constant comparative method and thematic analysis and triangulated to organize the themes and concepts for the proposed model. The outcome of the analytical process is theorized into an adoption model and grounded in the literature. The findings of the research provide very useful and practical model for administrators to stimulate Faculty motivation as they embark on BL implementation. The model indicates that external and internal environmental factors stimulate Faculty motivation to make a choice regarding the teaching modalities they prefer. It posits that as Faculty members begin to implement teaching process using technology, they become sensitized and begin to internalize the differences between the two teaching modalities/models and thus decide to adopt BL based on the level of implicit and explicit motivational factors that exist within the faculty members and the university.